The relationship of body mass index and motor abilities of eight grade students - Ivana Martinčević; Nera Žigić; Igor Mraz; Nikola Sedlar (University of Banja Luka, Faculty of physical education and sport, 2022)
The aim of this research was to examine the connection of body mass index of eighth grade students and their results in motor abilities test, with the purpose of gaining insight in which tests is that connection more or less expressed, or there isn't any. The sample of subjects consisted of 66 male and 64 female students from four elementary schools from the Varaždin city area, who attended eighth grade in the school year of 2018/2019 For data analysis, the results of the final testing of motor abilities were used. The sample of variables consisted of six motor tests and two anthropometrical measures, student's age and their body mass index. For all 10 variables the basic descriptive parameters were calculated (arithmetic mean, standard deviation, minimum and maximum), both for female and male students. Further data processing was done by linear regression analysis - 6 x regression analysis for each motor ability. The results of the regression analysis in male students showed statistically significant connection of body mass index and four variables (standing long jump, shuttle run with carrying objects, sit and reach and pull-up hold), while in female students the connection was significant only in two variables (standing long jump and pull-up hold). Overweight and obesity of children and adolescents is a growing phenomenon all over the world. Motor abilities are an important indicator of physical activity and one of the possible indicators of the level of fitness. Overweight and obesity, as well as underweight, negatively influence the condition and development of motor abilities, and the role of Physical education classes are of great importance in prevention and promotion of healthy living habits of students.